Brain dynamics of (a)typical reading development—a review of longitudinal studies - Katarzyna Chyl (Nature Portfolio, 2021)
Abstract Literacy development is a process rather than a single event and thus should be studied at multiple time points. A longitudinal design employing neuroimaging methods offers the possibility to identify neural changes associated with reading development, and to reveal early markers of dyslexia. The core of this review is a summary of findings from longitudinal neuroimaging studies on typical and atypical reading development. Studies focused on the prediction of reading gains with a single neuroimaging time point complement this review. Evidence from structural studies suggests that reading development results in increased structural integrity and functional specialization of left-hemispheric language areas. Compromised integrity of some of these tracts in children at risk for dyslexia might be compensated by higher anatomical connectivity in the homologous right hemisphere tracts. Regarding function, activation in phonological and audiovisual integration areas and growing sensitivity to print in the ventral occipito-temporal cortex (vOT) seem to be relevant neurodevelopmental markers of successful reading acquisition. Atypical vOT responses at the beginning of reading training and infant auditory brain potentials have been proposed as neuroimaging predictors of dyslexia that can complement behavioral measures. Besides these insights, longitudinal neuroimaging studies on reading and dyslexia are still relatively scarce and small sample sizes raise legitimate concerns about the reliability of the results. This review discusses the challenges of these studies and provides recommendations to improve this research area. Future longitudinal research with larger sample sizes are needed to improve our knowledge of typical and atypical reading neurodevelopment.